Общественное мнение: критерии идентификации - Матусевич, В. (Социология: теория, методы, маркетинг, 2000)
To determine the identification criteria of public opinion, in order to identify it in contrast to other very similar (as to certain features) objects, is important in theoretical and practical aspects. According to the author, the initial principle of the definition should be an understanding that public opinion has two connected dimensions: outer one, which can be revealed in attitudes of social subject (community) toward an object(socially important problem, event, etc.), and inner one, which can be revealed in organization of these attitudes by social control means. Due to the analysis of public opinion (conducted in the context of social control, role theory and referent groups theory, identification and self-categorization concepts), there was brought out a series of features capable of being used for identification criteria determination after they would be reduced to methodical means.